Pelatihan Penggunaan Aplikasi Multimedia Pembelajaran berbasis Artificial Intelligency (AI) Guru SMK Elanus Ruteng - Danu, Angela Klaudia; Dwianot Momang, Handrianus; Yuliantari, Ans Prawati; Sii, Petrus; Rampung, Bonefasius (Jurnal SOLMA, 2024)
Background: This PKM Prodi research discusses training for teachers in the use of Artificial Intelligence (AI) multimedia in learning. The role of multimedia in education is becoming increasingly important to emphasise learning outcomes. The main objective of this research is to train teachers at SMK Elanus Karot Ruteng to use AI-based multimedia learning applications. This research focuses on training teachers at SMK ElanusRuteng in the use of AI-based learning multimedia applications, involving a total of 18 people and will take place over 3 days of activities. Method: The methods in the research are: training planning, training implementation, programme implementation evaluation assistance, programme sustainability evaluation. Result: Teachers can use AI applications to create learning material products in the form of PowerPoint presentations, short stories, graphics, images and learning videos that support more interesting subject matter. Increased ability and skills in the use of information technology and web-based learning media for teachers to support the learning process, resulting in increased student participation and understanding of the material. Conclusion: From this research, it can be concluded that teachers are collaborating to be more innovative and adaptable to technological advances that affect education. This collaboration with Artificial Intelligence must, of course, be adapted to valid and up-to-date references according to the needs of the material.